Re-evaluating emergency water supply in 'complex droughts' in Africa - Sarah Moss (2003)
This paper presents the findings from a recent field survey in Mulanje district in Malawi, which suggests the need for a re-evaluation of traditional emergency water supply interventions in some ‘droughts’.